Semileptonic hyperon decays and Cabibbo-Kobayashi-Maskawa unitarity - Cabibbo, Nicola; Swallow, Earl C; Winston, Roland (Physical review letters, 2004)
Using a technique that is not subject to first-order SU(3) symmetry breaking effects, we determine the V(us) element of the Cabibbo-Kobayashi-Maskawa matrix from data on semileptonic hyperon decays. We obtain V(us)=0.2250(27), where the quoted uncertainty is purely experimental. This value is of similar experimental precision to the one derived from K(l3), but it is higher and thus in better agreement with the unitarity requirement, |V(ud)|(2)+|V(us)|(2)+|V(ub)|(2)=1. An overall fit, including the axial contributions and neglecting SU(3) breaking corrections, yields F+D=1.2670 +/-0.0035 and F-D=-0.341+/-0.016 with chi(2)=2.96/3 degrees of freedom.